Visiting and office home care workers' occupational health: An analysis of workplace flexibility and worker insecurity measures associated with emotional and physical health - Isik U. Zeytinoglu; Margaret Denton; Sharon Davies; M. Bianca Seaton; Jennifer Millen (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2009)
The home health care sector in Canada experienced major restructuring in the mid-1990s creating a variety of flexibilities for organizations and insecurities for workers. This paper examines the emotional and physical health consequences of employer flexibilities and worker insecurities on home health care workers. For emotional health the focus is on stress and for physical health the focus is on selfreported musculoskeletal disorders. Data come from our survey of home health care workers in a mid-sized city in Ontario, Canada. Data are analyzed separately for 990 visiting and 300 office workers. For visiting workers, results showed that none of the objective flexibility/insecurity measures are associated with stress or musculoskeletal disorders controlling for other factors. However, subjective flexibility/insecurity factors, i.e. feelings of job insecurity and labour market insecurity, are significantly and positively associated with stress. When stress is included in the analysis, for visiting workers stress mediates the effects of subjective flexibility/insecurity with musculoskeletal disorders. For office workers, none of the objective flexibility/insecurity factors are associated with stress but subjective flexibility/insecurity factor of feelings of job insecurity is positively and significantly associated with stress. For office home care workers, work on call is negatively and significantly associated with musculoskeletal disorders. Feeling job insecurity is mediated through stress in affecting musculoskeletal disorders. Feeling labour market insecurity is significantly and positively associated with musculoskeletal disorders for office home care workers. Decision-makers in home care field are recommended to pay attention to insecurities felt by workers to reduce occupational health problems of stress and musculoskeletal disorders.
Keywords: I11; J28; 330; home health care workers; stress; worker insecurity; Pflegedienst; Arbeitsbedingungen; Betriebliches Gesundheitsmanagement; Kanada